Improving spatio-temporal benefit transfers for pest control by generalist predators in cotton in the southwestern US. Issue 1 (1st January 2017) - Wiederholt, Ruscena; Bagstad, Kenneth J.; McCracken, Gary F.; Diffendorfer, Jay E.; Loomis, John B.; Semmens, Darius J.; Russell, Amy L.; Sansone, Chris; LaSharr, Kelsie; Cryan, Paul; Reynoso, Claudia; Medellín, Rodrigo A.; et al.
ABSTRACT: Given rapid changes in agricultural practice, it is critical to understand how alterations in ecological, technological, and economic conditions over time and space impact ecosystem services in agroecosystems. Here, we present a benefit transfer approach to quantify cotton pest-control services provided by a generalist predator, the Mexican free-tailed bat ( Tadarida brasiliensis mexicana ), in the southwestern United States. We show that pest-control estimates derived using (1) a compound spatial – temporal model – which incorporates spatial and temporal variability in crop pest-control service values – are likely to exhibit less error than those derived using (2) a simple-spatial model (i.e., a model that extrapolates values derived for one area directly, without adjustment, to other areas) or (3) a simple-temporal model (i.e., a model that extrapolates data from a few points in time over longer time periods). Using our compound spatial–temporal approach, the annualized pest-control value was $12.2 million, in contrast to an estimate of $70.1 million (5.7 times greater), obtained from the simple-spatial approach. Using estimates from one year (simple-temporal approach) revealed large value differences (0.4 times smaller to 2 times greater). Finally, we present a detailed protocol for valuing pest-control services, which can be used to develop robust pest-control transfer functions for generalist predators in agroecosystems.EDITED BY Neville Crossman